COMMUNITY SERVICE THROUGH THE KPM PROGRAM OF GUNUNG LEUSER UNIVERSITY IN DARUL AMIN VILLAGE, SOUTHEAST ACEH REGENCY - Zaini Hasan; Anton Purnama; Ladipin Ladipin; Orbit Irwansyah; Habibul Akram (CV. Armas Suan Sejahtera, 2025)
Community service is an important effort in strengthening the relationship between universities and the community. This article discusses the Community Service Program through the Community Service Lecture Program (KPM) of Gunung Leuser University in Darul Amin Village, Southeast Aceh Regency. The introduction of this article highlights the importance of community service in the context of higher education and society. The objective of this program is to improve the quality of life for the community through various activities that involve active participation from the community itself. The community service method employed is Participation Action Research (PAR), which involves active community participation in the research process and implementation of solutions. Through PAR steps such as joint problem identification, planning, action, and joint reflection, the community and students collaborate to identify the main issues in Darul Amin Village and design solutions that align with the community's needs and aspirations. The results of this program demonstrate significant improvements in community participation, strengthened local capacity, and sustainable problem-solving. The conclusion of this article emphasizes the importance of collaboration between universities and communities in enhancing collective well-being and highlights the success of the PAR approach in achieving community service objectives.